Pengaruh Penerapan Model Pembelajaran STM (Sains, Teknologi, Masyarakat) Menggunakan Media Peta Konsep Terhadap Minat Belajar - Hayati Nufus; Yuni Fatisa (Konfigurasi : Jurnal Pendidikan Kimia dan Terapan, 2017)
The goal of this study was to find out the effect of the implementation of science, technology, and society (STS) learning model by using concept maps toward students’ learning interest in Islamic Senior High School. Therefore, the study was carried out in queasy experiment design and the sample was taken through purposive sampling technique, which consists of two classes, namely XC as experiment class and XB as control one. After implementing those learning model and technique, the data was collected through questionnaire and documentation. Due to the statistic analysis, it was examined that the implementation of concept maps technique on experiment class has affected students’ interest in learning 81.45%, and it was categorized into good, in contrast, in control group it has affected students’ interest about 61.2% that was categorized into Fair. Similarity, the hypothesis testing by using Mann-Whitney test on the final questionnaire average score has revealed that the Zo (t-obtained) score was -5.74 and Z table score was -1.96 based on 5% significant standard, further, when Zo ≤-Z table, the null hypothesis was rejected and the alternative hypothesis was accepted. In conclusion, there was the significant effect of science, technology, and society (STS) learning model by using concept maps technique toward students’ learning interest in Hydrocarbon class in Islamic Senior High School of Islamic Boarding School Daarun Nahdhah Thawalib Bangkinang for the 2015/2016 academic year.Keywords : Science, Technology, Society (STS) teaching model, concept maps techniques, students’ learning Interest, and hydrocarbon.